Hubungan Kualitas Layanan, Pengalaman Konsumen, Kepuasan Konsumen, dan Loyalitas Konsumen: Model Konseptual - Friska Mastarida (Forum Kerjasama Pendidikan Tinggi, 2023)
The purpose of this article is to build a conceptual model, the status of each variable, and hypotheses. This article describes the variables that affect consumer loyalty. This study uses a qualitative research design through causal-explanatory techniques. The research findings found that the more emotional the consumer's experience is which is influenced by the consumer's value for carrying out purchasing activities, the stronger the desired level of customer satisfaction and loyalty will be. This area of research requires a great deal of attention, both theoretically and empirically, to analyze and develop new antecedents of consumer loyalty. This article provides a complete framework regarding the importance of analyzing and evaluating consumer behavior from pre-purchase, in purchase and post-purchase.